Audit Judgment: Analisis Persepsi Etis, Kompleksitas Tugas, dan Keyakinan Diri Auditor - Muslim; Andhika Febrianto; Rahim, Syamsuri (AkMen JURNAL ILMIAH, 2023)
udit judgment is the auditor's policy in determining an opinion regarding the results of the audit which refers to the formation of an idea. There are many ways that influence audit judgment. One of them is ethical perception, task complexity, and self-efficacy. This research aims to determine the influence of ethical perceptions, task complexity, and self-efficacy on audit judgment at the office of the Financial and Development Supervisory Agency representing South Sulawesi Province. The analytical method used to test the hypothesis is multiple linear regression. This analysis is based on data from 30 respondents who have completed all the statements in the questionnaire to provide an idea of ​​whether ethical perceptions, task complexity and self-efficacy have a significant influence or not. The results of this research indicate that ethical perceptions, task complexity, and self-efficacy partially influence the audit judgment of auditors at the Office of the Financial and Development Supervisory Agency (BPKP). These three variables have a positive influence.